ACTIVITY OF WATER AND ETHANOL Syzygium myrtifolium Walp. AS ANTIBACTERIAL Aggregatibacter actinomycetemcomitans - Deviana Adinda Nurfatimah; Risyandi Anwar; Puspito Ratih Hardhani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Background: One of the pathological conditions in the mouth that affects periodontal tissue is periodontitis. Aggregatibacter actinomycetemcomitans is a potential trigger of periodontal disease if allowed to settle, multiply, and express virulence factors. The pharmacological activity of Syzygium myrtifolium based on solvent extract has several functions, one of which is antibacterial. Solvents function to attract compounds or active ingredients in natural materials, and solvents are distinguished based on their polarity. Water is very polar, so it will attract compounds or active ingredients that are very polar, while ethanol is polar, so it will attract active substances/compounds that are polar. So that later it can be known how both perform. Objective: This study aims to determine the activity of water and ethanol extracts of Syzygium myrtifolium Walp. 10%, 20%, 40%, and 80% in inhibiting the growth of Aggregatibacter actinomycetemcomitans bacteria. Materials and Methods: This study is a laboratory experiment. Ethanol extract of Syzygium myrtifolium Walp. was partitioned to obtain a water extract of Syzygium myrtifolium Walp. A disc diffusion method on Mueller Hinton Agar (MHA) media was the antibacterial test method used in this study (n=4). Metronidazole 50 µg was used as a positive control and DMSO 2% as a negative control. Results: The average inhibition zone of ethanol extract was 9.11 mm, 11.475 mm, 13.625 mm, and 15.2875 mm, respectively, while the water extract was 10.3125 mm, 13.25 mm, 14.725 mm, and 16.725 mm, respectively. Positive control 22.975 mm and negative control 0 mm. Conclusion: Water and ethanol extracts of Syzygium myrtifolium Walp. have antibacterial activity against Aggregatibacter actinomycetemcomitans.